Scenario for near-term implementation of partial capture from blast furnace gases in Swedish steel industry - Biermann, Max; Normann, Fredrik; Johnsson, Filip; Larsson, Mikael; Bellqvist, David; Skagestad, Ragnhild; Ali, Hassan (2019)
Iron-and-steel making is a carbon-intensive industry and responsible for about 8% of global CO2 emissions. Meeting CO2 reduction targets is challenging, since carbon is inherent in the dominating production route in blast furnaces. Long-term plans to phase out carbon and change production technique are under way, such as iron ore reduction with hydrogen[1][2] won from renewable energies or electro winning[3], however unlikely to be implemented at scale before 2040 [4]. Until a transition to such technologies is completed, carbon leakage will remain to be a threat to steel industry inside EU ETS system. CCS remains an option for steel industry to comply with reduction targets and meet rising allowance (EUA) prices, currently above 20 €/t. Most studies on CCS propose a capture rate of ≥ 90 %[5–7], however, CCS could be considered as a part of a series of measures (e.g. fuel change, energy efficiency measures) that together achieve a significant reduction in CO2 emissions until a carbon-neutral production is in place. This line of thought motivates the concept of partial capture, where only the most cost effective part of the CO2 emissions are separated for storage [8]. In steel industry, high CO2 concentrations at large flows and the availability of excess heat make partial capture attractive. Previous work on the steel mill in Luleå, Sweden, emits around 3.1 Mt CO2 per year, has found that 40-45 % of site emissions can be captured fueled by excess heat alone[9]. Therein, five heat recovery technologies were assessed, ranging from back pressure operation of CHP turbine to dry slag granulation. Promising CO2 sources on site include flue gases from hot stoves and the combined-heat and power plant, and the process gas originating from the blast furnace – blast furnace gas (BFG). BFG is a pressurized, low value fuel used for heating on site. CO2 separation from BFG requires less reboiler heat for MEA regeneration, and the enhanced heating value of the CO2 lean BFG increases energy efficiency of the steel mill [9].This ...